Identification of Threats To The Sustainability of Smallholder Dairy Farming Using A Multidimensional Risk Perspective - Erma Malika, Uyun; Ahmad Hudori, Huda; Perlambang CNAWP, Rizal; Prasetyo, Budi (International Journal of Science, Technology & Management, 2025)
The sustainability of dairy cattle businesses in smallholder farms faces various complex and interconnected threats, especially after the outbreak of Foot-and-Mouth Disease, which worsened the national cattle population and milk production. This research aims to identify threats to the sustainability of dairy cattle businesses in Suci Village, Panti District, Jember, using a multidimensional risk approach that includes ecological, economic, social, technological, and institutional dimensions. A quantitative approach was used with a census method on 25 dairy farmers as respondents, using a structured questionnaire. The research results indicate that the majority of dairy farms fall into the "less sustainable" category, characterized by low availability of green fodder, barn capacity, number of livestock, income, education level, farming experience, group role, and low technology utilization. Leverage analysis identifies several sensitive attributes that most influence sustainability levels, namely agricultural waste utilization (ecological), number of livestock (economic), education and farming experience (social), group role (institutional), and mobile phone usage (technological). These findings highlight the need for comprehensive interventions in farmer capacity building, institutional strengthening, technology modernization, and improved feed and waste management to promote the sustainability of smallholder dairy farming at the village level.